Groundwater governance and adoption of solar-powered irrigation pumps: experiences from the eastern Gangetic Plains - Bastakoti, Ram C.; Raut, Manita; Thapa, Bhesh Raj (World Bank, 2020)
Solar-powered irrigation pumps (SPIPs) have been promoted in the Eastern Gangetic Plains (EGP) in recent decades, but rates of adoption are low. This case study assesses the evidence from several solar pump business models being adopted in parts of the EGP, particularly eastern Nepal and northern India, and explores how different models perform in various contexts. It documents lessons for increasing farmers’ resilience to droughts through better groundwater use by promotion of SPIPs. Groundwater access for agriculture in the past was dependent on diesel and electric pumps, respectively constrained by costs and reliability of energy. Both government and nongovernment agencies have promoted SPIPs in the Ganges basin for irrigation and drinking purposes. SPIPs receive different levels of subsidies across countries and states in the region to facilitate adoption and ensure continuous and timely irrigation, which particularly benefits small and marginal farmers. Because the EGP faces variability in water availability, the SPIPs could help in building drought resilience. However, because low operating costs for SPIPs does little to incentivize farmers to use water efficiently, one critical question is how to balance equitable access to SPIPs while ensuring groundwater overdraft is not perpetuated. Farmers’ awareness of efficient water management options is crucial to avoid overextraction of groundwater.